Dutch Treat Dutch National Ballet - Apter, Kelly (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Dutch National Ballet at the Edinburgh Festival. PALABRAS CLAVE: Dutch National Ballet, Edinburgh internacional Festival, Scottish Ballet, La valse, The Grey Area, The Concert.